Blood‐based protein predictors of dementia severity as measured by δ: Replication across biofluids and cohorts. Issue 1 (1st December 2019) - Royall, Donald R.; Bishnoi, Ram J.; Palmer, Raymond F.; ,; Pavlik, Valory; Massman, Paul; Darby, Eveleen; Rodriguear, Monica; Ansari, Aisha Khaleeq; DeToledo, John C.; Reddy, Hemachandra; Wilms, Henrick; et al.
Abstract: Introduction: Dementia severity can be empirically described by the latent dementia phenotype "δ" and its various composite "homologs". We have explored δ's blood‐based protein biomarkers in the Texas Alzheimer's Research and Care Consortium (TARCC) study. However, it would be convenient to replicate those associations in the Alzheimer's Disease Neuroimaging Initiative (ADNI). To this end, we recently engineered a δ homolog from observed cognitive performance measures common to both projects (i.e., "dT2A"). Methods: We used nine rationally chosen peripheral blood‐based protein biomarkers as indicators of a latent variable "INFLAMMATION". We then associated that construct with dT2A in structural equation models adjusted for age, gender, depressive symptoms, and apolipoprotein E (APOE) ε4 allelic burden. Significant factor loadings and INFLAMMATION's association with dT2A were confirmed in random splits of TARCC's relatively large sample, and across biofluids in the ADNI. Results: Nine proteins measured in serum (TARCC) or plasma (ADNI) explained ≅10% of dT2A's variance in both samples, independently of age, APOE, education, and gender. All loaded significantly on INFLAMMATION, and positively or negatively, depending on their known roles are PRO‐ or ANTI‐inflammatory proteins, respectively. The parameters of interest were confirmed across random 50% splits of the TARCC's sample, and replicated across biofluids in the ADNI. Discussion: These results suggest that SEM can be used to replicate biomarker findings across samples and biofluids, and that a substantial fraction of dementia's variance is attributable to peripheral blood‐based protein levels.